2017
DOI: 10.1111/andr.12417
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of pre‐operative inflammation‐based prognostic scores (neutrophil‐to‐lymphocyte ratio, platelet‐to‐lymphocyte ratio, and monocyte‐to‐eosinophil ratio) in testicular sperm extraction: a pilot study

Abstract: To investigate the ability of some hematologic prognostic scores demonstrating inflammation in predicting sperm presence in testicular sperm extraction (TESE). We retrospectively investigated the medical data of 430 patients with the diagnosis of non-obstruc tive azoospermia (NOA) who had undergone TESE operation consecutively in our institution between the dates of January 2009 and February 2017. In all, 352 patients with the diagnosis of NOA, with bilaterally palpable vas deferens, who had undergone TESE for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 18 publications
1
31
0
3
Order By: Relevance
“…Likewise, our findings (Ventimiglia et al, 2018). Another study demonstrated that systemic inflammation negatively affects the possibility of sperm retrieval in TESE (Yucel et al, 2017).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Likewise, our findings (Ventimiglia et al, 2018). Another study demonstrated that systemic inflammation negatively affects the possibility of sperm retrieval in TESE (Yucel et al, 2017).…”
Section: Discussionsupporting
confidence: 82%
“…Our study revealed a cutoff value of 1.8 (AUC 0.712, p < 0.001; sensitivity 61.1%; specificity 75.0%) discrimination of the phases of PD for the NLR. Various cutoff values have been found in different studies for NLR ranged between 1 and 5 (Nishida et al ., ; Yucel et al ., ; Ventimiglia et al ., ). Forget et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…According to the literature, the rate of sperm retrieval in patients with NOA undergoing mTESE is around 50% (Vloeberghs et al, ). The success of the operation depends on many factors (Yucel et al, ), including seasonal variations in numerous physical and psychological factors, including reproduction. This, in turn, has drawn attention to the relationship between seasonal variation and sperm quality.…”
Section: Introductionmentioning
confidence: 99%